(untitled) (Pedagogical Horizons, 2023)
The penetration of society and thus also of schools with media also poses new challenges for teachers. Teachers are required to acquire media-related knowledge in the third phase of education, in-service training, in order to be able to offer contemporary teaching with digital devices and media options such as distance teaching. Through a post-then-pre-evaluation, the impact of the online training initiative "iPad Innovation Series" was examined in the present study with regard to media competence and digital competence and possible influencing factors were localised. The increase in media competence/digital literacy was particularly high among people with more professional experience, with previous knowledge in the use of media in the classroom and among those who actively participated in the training by creating a product. A positive correlation was also found with regard to the intrinsic motivation to participate in the training, to hold it as an online training and especially the influence of the instructors.